The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.32843/infrastruct67-20
|View full text |Cite
|
Sign up to set email alerts
|

Employer Brand of Food Industry Enterprises

Abstract: The questions related to the forming of employer brand of enterprises of food industry for maintenance of business reputation and further engage and development of employees are investigated in the article. Today it is not enough material motivation for workers, additionally pulled out requirement to the development, management, certification, prosperity on international standards, participating in projects, and ratings. The construction of strong employer brand is the actual task of any enterprise in the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…O. Dragan (2022) found that the main criteria for selecting countries were demand for business products/services, developed infrastructure, and fewer legal barriers to company registration. As a result, the value of forming an employer brand for businesses increases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…O. Dragan (2022) found that the main criteria for selecting countries were demand for business products/services, developed infrastructure, and fewer legal barriers to company registration. As a result, the value of forming an employer brand for businesses increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…O. Dragan (2022) suggests distributing value propositions according to employee categories (by age or work area) and appropriate communication, which will become components of a successful employer brand. A. Savina & I. Torianyk proved that the employer's value proposition is the basis for increasing the attractiveness of working in the company.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2020) defines the employer brand as internal measures with effective feedback to employees, material and non-material motivation, an effective personnel evaluation system, the opportunity for employee development and training. Dragan, Solomka, Maznyk (2022) investigate the main factors and best practices of an employer brand formation in food industry enterprises. Varis, I., Kravchuk, O., Spirina, K. (2022) identified the main channels of employer brand promotion among Ukrainian companies.…”
Section: Introductionmentioning
confidence: 99%